Faith, Function, and Transformation: A Study of the Nuo Culture in Pingxiang, Jiangxi - Zhang, Jiahao (Pacific International Journal, 2025)
Nuo culture in Pingxiang, Jiangxi Province, represents one of China’s most enduring ritual traditions, integrating religious practices, theatrical performance, and community organization. Historically rooted in ancient exorcistic rites and shaped by the interactions between Central Plains civilization and southern ritual traditions, Pingxiang Nuo has developed into a unique cultural system characterized by its multilayered belief structure and its diverse social functions. Based on extensive textual analysis and fieldwork—including participant observation, temple visits, interviews with Nuo masters, artisans, officials, and local residents—this study examines the belief system, ritual symbolism, and sociocultural roles of Nuo practice in Pingxiang. It argues that the tradition simultaneously embodies a cosmological worldview, a moral education mechanism, a community-building institution, and a living heritage resource. However, rapid modernization, weakened clan structures, youth disinterest, and commercialized misappropriation have created unprecedented challenges, threatening the continuity of ritual knowledge and cultural authenticity. Using theories of ritual symbolism, social space, and folklore practice, this paper analyzes how Nuo culture has transitioned from a sacred community-based spiritual system to a public cultural asset in contemporary society. It further proposes strategies for sustainable transmission through education, policy support, community revitalization, and digital documentation. This research enriches the understanding of Chinese ritual culture and provides insights for global discussions on intangible cultural heritage preservation and the revitalization of rural cultural identity.